Collaborative research in organizations : foundations for learning, change, and theoretical development - 4 0 16; Adler, Niclas,;Shani, Abraham B.,;Styhre, Alexander; 5 (Thousand Oaks, California : Sage Publications, 2004)
A guide to using collaborative research in organizations that provides information on the history of collaborative research, its impact on the business world, the challenges it poses, and other related topics.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Research. -- Management;Research teams. -- 20; 20; 2